Distributed leadership, team working and service improvement in healthcare. Issue 4 (5th October 2015) - Boak, George; Dickens, Victoria; Newson, Annalisa; Brown, Louise
Abstract : Purpose: – The purpose of this paper is to analyse the introduction of distributed leadership and team working in a therapy department in a healthcare organisation and to explore the factors that enabled the introduction to be successful. Design/methodology/approach: – This paper used a case study methodology. Qualitative and quantitative information was gathered from one physiotherapy department over a period of 24 months. Findings: – Distributed leadership and team working were central to a number of system changes that were initiated by the department, which led to improvements in patient waiting times for therapy. The paper identifies six factors that appear to have influenced the successful introduction of distributed learning and team working in this case. Research limitations/implications: – This is a single case study. It would be interesting to explore whether these factors are found in other cases where distributed leadership is introduced in healthcare organisations. Practical implications: – The paper provides an example of successful introduction of distributed leadership, which has had a positive impact on services to patients. Other therapy teams may consider how the approach may be adopted or adapted to their own circumstances. Originality/value: – Although distributed leadership is thought to be important in healthcare, particularly when organisational change is needed, there are very few studies of the practicalities of how it can be introduced.